2018
DOI: 10.6028/nist.ams.100-17
|View full text |Cite
|
Sign up to set email alerts
|

The influence of spreading metal powders with different particle size distributions on the powder bed density in laser-based powder bed fusion processes

Abstract: In laser powder bed fusion (LPBF) processes, the powder size characteristics, like particle shape, particle size (PS), particle size distribution (PSD), and the resulting powder bed density (PBD), are key influencing factors of the built material properties. To better understand the correlations between the powder size characteristics and the powder properties influencing the LPBF process, apparent density (AD), flowability, and PBD were measured corresponding to two commercial metal powders with different PS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 7 publications
3
38
0
1
Order By: Relevance
“…Consequently, the non-lling of the voids occurs between the larger particles by the ne particles and eventually causes the creation of the cavities. These results are consistent with a report by Jacob et al [52] who found that ner particles moved away from larger particles by accumulating in the lower layers of the powder bed.…”
Section: Characterization Of Composite Componentssupporting
confidence: 93%
“…Consequently, the non-lling of the voids occurs between the larger particles by the ne particles and eventually causes the creation of the cavities. These results are consistent with a report by Jacob et al [52] who found that ner particles moved away from larger particles by accumulating in the lower layers of the powder bed.…”
Section: Characterization Of Composite Componentssupporting
confidence: 93%
“…These changes in the powder bed density are due to the differences in the powder spreading conditions for different layer thicknesses as demonstrated in [31]. If a layer thickness is smaller than the D90 value of the powder particle distribution [32], the density increases because the biggest particles are kept at the top of the layer and finally swept out by the recoater [33], which increases the powder bed density. It can be seen from Figure 6 that the higher the powder bed density (70%, Figure 6b, instead of 60%, Figure 6a), the higher the optimal laser power density, while the lower the build rate of the process.…”
Section: Density Of the Same Alloy Printed With Two Different Layer Tmentioning
confidence: 99%
“…because the biggest particles are kept at the top of the layer and finally swept out by the recoater [33], which increases the powder bed density. It can be seen from Figure 6 that the higher the powder bed density (70%, Figure 6b, instead of 60%, Figure 6a), the higher the optimal laser power density, while the lower the build rate of the process.…”
Section: Density Of the Same Alloy Printed With Two Different Layer Tmentioning
confidence: 99%
“…It is established that the higher the powder packing density, the higher the bed thermal conductivity, and the better the mechanical properties of the part [ 4 ]. Jacob et al [ 11 ] found that powders with a wide PSD increase the density of layer packing and decrease the flowability, which is crucial to powder spreading. Liu et al [ 12 ] revealed that gas-atomized 316L steel powder with a narrow PSD provides an improved flowability, leading to a high ultimate tensile strength and robust printed components.…”
Section: Introductionmentioning
confidence: 99%